Marine viruses disperse bidirectionally along the natural water cycle - Janina Rahlff; Sarah P. Esser; Julia Plewka; Mara Elena Heinrichs; André Soares; Claudio Scarchilli; Paolo Grigioni; Heike Wex; Helge-Ansgar Giebel; Alexander J. Probst (Nature Communications, 2023)
Abstract Marine viruses in seawater have frequently been studied, yet their dispersal from neuston ecosystems at the air-sea interface towards the atmosphere remains a knowledge gap. Here, we show that 6.2% of the studied virus population were shared between air-sea interface ecosystems and rainwater. Virus enrichment in the 1-mm thin surface microlayer and sea foams happened selectively, and variant analysis proved virus transfer to aerosols collected at ~2 m height above sea level and rain. Viruses detected in rain and these aerosols showed a significantly higher percent G/C base content compared to marine viruses. CRISPR spacer matches of marine prokaryotes to foreign viruses from rainwater prove regular virus-host encounters at the air-sea interface. Our findings on aerosolization, adaptations, and dispersal support transmission of viruses along the natural water cycle.